1981
DOI: 10.1177/001872088102300206
|View full text |Cite
|
Sign up to set email alerts
|

Drivers' Steering Behavior When Meeting Another Car: The Case of Perceptual Tropism Revisited

Abstract: It was reported in a recent paper that, when meeting another car, drivers start turning the steering wheel left 2 s before the meeting, indicating, according to the authors explanation, approaching behavior due to the perceptual significance of the oncoming car. The current study was conducted to test an alternative correction-maneuver explanation. The lateral position of passing cars was recorded at several measurement points on two-lane roads, and the mean value was plotted as a function of the time from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This overall "reorientation" path strategy was first proposed by Triggs (1980). This hypothesis was later supported by Summala, Leino, and Viermaa (1981). Data reported in these two studies refuted the claim by Helander (1978), based on patterns of steering wheel movements, that drivers tend to steer their cars towards approaching vehicles during the last 2 s before meeting.…”
Section: Selecting Vehicle Approach Pathmentioning
confidence: 52%
“…This overall "reorientation" path strategy was first proposed by Triggs (1980). This hypothesis was later supported by Summala, Leino, and Viermaa (1981). Data reported in these two studies refuted the claim by Helander (1978), based on patterns of steering wheel movements, that drivers tend to steer their cars towards approaching vehicles during the last 2 s before meeting.…”
Section: Selecting Vehicle Approach Pathmentioning
confidence: 52%
“…HPRT could further be broken into brake-perception response time (BPRT) or steering-perception response time (SPRT) when capturing individual brake or steering response latencies. Most studies have focused on evaluating BPRT [124], whereas a few studies have also reported SPRT [125,126,127] There has been extensive research that has investigated the effect of different factors that influence drivers HPRT [124,128,129]. Factors commonly investigated include: age and experience of drivers [122,130], peculiarity of hazards [131,132], effects of distraction [133,134,135], and scenarios involving transfer of control from automated driving [136].…”
Section: Introduction To Study IImentioning
confidence: 99%